Challenging the salvation stories of music education: Adolescent music school students narrating their musical ecosystems - Backer Johnsen, Hanna (Sage, 2026)
Music education tends to portray marginalized students—for example those with foreign backgrounds or from low-income families—as needing to be “saved” by music education. While these stories are potentially helpful when securing funding and promoting socially driven initiatives as part of institutions’ inclusive aims, they simultaneously risk obscuring the complexities of meaningful music-making and overlook the lived experiences of the young people involved, thereby perpetuating structural inequities. This article addresses the question of inclusion from the perspective of students themselves by exploring adolescents’ experiences in Floora, a social innovation within the Basic Education in the Arts music system in Finland, providing access to regular instrumental tuition at music schools for children and young people who would not otherwise be able to participate due to socio-economic barriers. The empirical material has been generated through interviews with adolescents in Floora and analyzed through narrative inquiry. The findings articulate how students’ experiences of regular music tuition do not align with benevolent professional salvation stories. Rather, the findings point to the complexity of meanings given to music-making and instrumental learning, creating a whole ecosystem of social and musical encounters where agency can be achieved or challenged far beyond music schools. Recognizing the multiplicity of young people’s musical worlds and viewing these worlds as interconnected requires professional responsibility and genuine knowledge sharing among all involved, fostering the potential for social justice and more democratic practices within music schools.
Keywords: music education; young people; music schools; school children; children (age groups); inequality; inclusion; social justice